PEMBELAJARAN ACTIVE LEARNING UNTUK MENINGKATKAN GAIRAH BELAJAR BAHASA SUNDA DI SDN KENCANA 3 KOTA BOGOR - Yuyus Rustandi; Prapto Waluyo (Universitas Pakuan, 2022)
Sundanese as one of the largest regional languages in Indonesia after Javanese is increasingly being eroded due to the demands of an increasingly advanced era has resulted in less attention being paid to Sundanese language subjects at every level of education. To increase the passion for learning Sundanese subjects, especially at SDN Kencana 3, Bogor City, try to use active learning learning methods, so there are interesting things to research, considering the location of the school is in a heterogeneous elite housing complex environment from various provinces throughout Indonesia. Even the area outside the complex that surrounds it in terms of the use of everyday language is closer to the Betawi language area, but by using active learning the value of students' academic achievement in Sundanese subjects shows good and satisfactory results.